The virtual reality model of mathematical word problems for autistic children - Rosli, Zareena (2025)
This research focuses on improving contextual knowledge and problem-solving skills in daily math activities for autistic children. The study developed and evaluated a Virtual Reality Model (VRMath). This model combines constructivism, situated learning theory, and Mayer's Cognitive Theory of Multimedia Learning to create an engaging and interactive learning experience. These theories support the design of VRMath, which helps students learn meaningfully through active participation, real-world context, and improved multimedia presentation. The main objective is to explore how VRMath affects learners' contextual understanding, mental representation, and problem-solving abilities. A mixed-methods design was used, combining quantitative and qualitative approaches. The quantitative part employed a single-subject research design; the qualitative aspect included semi-structured interviews and participant observation. Three autistic children, aged 9 to 10 years, were purposefully selected based on their ASD profiles. The subjects received individualized instruction and intervention over a three-month period. Findings show that VRMath significantly improved the subjects contextual knowledge and problem-solving skills. The key contribution of this research is demonstrating the potential of virtual reality as an effective educational tool for autistic children. This enriches the Body of Knowledge (BOK) in special education and educational technology. This study provides valuable insights for educators and researchers looking for innovative ways to support the diverse learning needs of autistic students.